Identifikasi Tumbuhan Famili Amaranthaceae di Jepara - Nugrahaeni, Anisa Widya; Lita, Safira Nurul; Wulandari, Eka Ayu; elfatul rohmah, Elfatul Rohmah; Fitriyah, Fikri Aida; Muhamad Jalil, Muhamad Jalil (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
Spinach plants as leaf vegetables have long been known and loved by the wider community. However, the impact is very large in terms of improving the household economy, especially the provision of nutritious food and also a source of family income. Data collection uses documentation, identification, and observation. This research was conducted in Troso Village, Pecangaan District, Jepara Regency. The height of the place meters above sea level. The research was carried out with field observations of 21 points. The research method used was the identification of each species of spinach consisting of Sand Spinach (Cyathula prostrata) = 182 species, Thorn Spinach (Amaranthus spinosus) = 2 species, Red Spinach (Amaranthus retroflexus) = 75 species, Boroco (Celosia Argentea) = 22 species , Flower knop (Gomphrena goblosa) = 23 species, Bunga Kremah (Altenathera Sesillis) = 121 species, Jorong (Achyranthes Aspera) = 15 species. The results of the research show that there are many plant species of the Amanranthaceae family. The plant species found will be identified based on their morphological characteristics.